A Critical Analysis of Estonian Destination Branding since 1991 - Lenskaja, Julia (2009)
Developing a coherent and comprehensive country brand is of vital importance for the Central and Eastern European countries as branding can contribute to the increase of the number of tourists, involvement of foreign investments and the creation of favourable basis for product export etc. In 2001-2002 Estonia has been the forerunner of strategically developing, launching and coordinating a country brand (Szondi, 2007). However, in short time the favourable position was lost and the project was suspended. At this time, Estonian branding project was too immature to face the real challenges of branding, such as lack of experts and financial resources, political influences, negative criticism from community and media. Almost 6 years later, Estonia has acknowledged that having a strong country brand is crucial for surviving global competition. Today, the brand Estonia got a second life and is ready to learn from its own mistakes.